2007
DOI: 10.1097/hjr.0b013e3282efaf38
|View full text |Cite
|
Sign up to set email alerts
|

Safety and magnitude of changes in blood glucose levels following exercise performed in the fasted and the postprandial state in men with type 2 diabetes

Abstract: Our observations not only demonstrate that it was safe for middle-aged obese men with type 2 diabetes to exercise in the FS, but also show that the decrease in BGL during aerobic exercise was largely dependent on preexercise BGL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 24 publications
1
50
0
2
Order By: Relevance
“…An extensive review of the beneficial effects of PA in persons with a metabolic disease can be found in a recent report by the Physical Activity Guidelines Advisory Committee published by the United States Department of Health and Human Services (Physical Activity Guidelines Advisory Committee 2008). While several authors have commented previously on the CVD event risks associated with exercise in diabetes (Constantini et al 2005;Flood and Constance 2002;Chipkin et al 2001;Albert and Bernbaum 1995;Draznin 2000;Gaudet-Savard et al 2007;Graham and Lasko-McCarthey 1990;Bernbaum et al 1989;Kanade et al 2006), no attempt has been made to systematically document the adverse events in persons with metabolic disease. As such, several questions remain with respect to PA and metabolic disease: (i) what are the risks associated with increased PA for each type of metabolic disease-condition; (ii) what are the absolute and relative contraindications of exercise that should be considered in screening individuals with a metabolic condition; and (iii) who is qualified to screen and prescribe such an exercise program?…”
Section: The Link Between Diabetes and Cvdmentioning
confidence: 99%
“…An extensive review of the beneficial effects of PA in persons with a metabolic disease can be found in a recent report by the Physical Activity Guidelines Advisory Committee published by the United States Department of Health and Human Services (Physical Activity Guidelines Advisory Committee 2008). While several authors have commented previously on the CVD event risks associated with exercise in diabetes (Constantini et al 2005;Flood and Constance 2002;Chipkin et al 2001;Albert and Bernbaum 1995;Draznin 2000;Gaudet-Savard et al 2007;Graham and Lasko-McCarthey 1990;Bernbaum et al 1989;Kanade et al 2006), no attempt has been made to systematically document the adverse events in persons with metabolic disease. As such, several questions remain with respect to PA and metabolic disease: (i) what are the risks associated with increased PA for each type of metabolic disease-condition; (ii) what are the absolute and relative contraindications of exercise that should be considered in screening individuals with a metabolic condition; and (iii) who is qualified to screen and prescribe such an exercise program?…”
Section: The Link Between Diabetes and Cvdmentioning
confidence: 99%
“…57 They found that post-meal exercise resulted in lower plasma glucose levels at the end of exercise compared to values at the same time point when subjects had walked pre-meal. Additional studies found post-meal exercise (1 hour moderate exercise 58 or a short bout of intense exercise) 59 resulted in reduced hyperglycemia in those with T2DM; however, the exercise did not commence immediately after meal consumption. Additionally, subjects with higher pre-exercise BG levels in both studies benefited the most from post-meal exercise.…”
Section: Mitigating the Glycemic Effect Of Food With Exer-cisementioning
confidence: 99%
“…50 However, compliance with current exercise recommendations is poor, with self-reported compliance rates of about 35% for those with T2DM. 51 Emerging evidence [52][53][54][55][56][57][58][59] suggests that a short bout of post-meal exercise in particular can attenuate the spike in BG after consumption of carbohydrates, which may be advantageous for those with and without diabetes, including those with dementia. Knowing that a short bout of exercise after consumption of a carbohydrate load could specifically decrease the spike in BG after carbohydrate consumption may be more motivating for compliance than exercising for general improvements in glycemic control.…”
Section: -47mentioning
confidence: 99%
“…Furthermore, it was shown that glucose concentrations during aerobic exercise depend on the pre-exercise glucose levels (Gaudet-Savard et al, 2007).…”
Section: Physical Exercise and Insulin Resistancementioning
confidence: 99%